Analysis of sustainable development goals, gender, and financial soundness: Evidence from listed banks in developing Asian countries - Indah Anisykurlillah; Hasan Mukhibad; Muhammad Khafid; Kuat Waluyo Jati; Muhammad Ihlashul'amal (Social Sciences and Humanities Open)
The purpose of this study is to prove empirically the influence of female board members on Environmental, Social, and Governance (ESG) disclosure and to examine the impact of ESG and female board members on bank financial sustainability. The sample includes the banks listed in developing Asian countries from 2015 to 2023. The ESG disclosure data was obtained through content analysis. The financial and board composition data was collected from the bank's annual reports. Panel regression analysis was used to analyze the data. The Dynamic Generalized Method of Moments (GMM) was employed to add robustness to the findings and to overcome endogeneity bias. We report that the percentage of female board members positively affects ESG disclosure. Female board members contribute to more conservative and ethical decisions that positively impact ESG disclosure. Board policies are made through consensus decisions among all board members. However, gender diversity can lead to less effective policies due to communication and coordination, negatively affecting financial soundness. Additionally, we report that ESG disclosure does not positively impact the financial soundness of the banks. Our results remain robust after addressing endogeneity issues in the model.